2006
DOI: 10.1002/jcc.20523
|View full text |Cite
|
Sign up to set email alerts
|

How resonance assists hydrogen bonding interactions: An energy decomposition analysis

Abstract: Block-localized wave function (BLW) method, which is a variant of the ab initio valence bond (VB) theory, was employed to explore the nature of resonance-assisted hydrogen bonds (RAHBs) and to investigate the mechanism of synergistic interplay between delocalization and hydrogen-bonding interactions. We examined the dimers of formic acid, formamide, 4-pyrimidinone, 2-pyridinone, 2-hydroxpyridine, and 2-hydroxycyclopenta-2,4-dien-1-one. In addition, we studied the interactions in -diketone enols with a simplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 71 publications
7
82
1
Order By: Relevance
“…We note that our estimate of ∆E int ) -18.9 kcal/mol for 3 is in good agreement with the MP2 value of -17.2 kcal/mol obtained by Beck and Mo. 63 These authors made use of decomposition scheme similar to that of Góra 62 et al They were only indirectly able to estimate a resonance energy ∆E π RAHB with a value of -12.3 kcal/mol, which seems very large in absolute terms.…”
Section: Resultssupporting
confidence: 82%
“…We note that our estimate of ∆E int ) -18.9 kcal/mol for 3 is in good agreement with the MP2 value of -17.2 kcal/mol obtained by Beck and Mo. 63 These authors made use of decomposition scheme similar to that of Góra 62 et al They were only indirectly able to estimate a resonance energy ∆E π RAHB with a value of -12.3 kcal/mol, which seems very large in absolute terms.…”
Section: Resultssupporting
confidence: 82%
“…However, a few theoretical studies were reported recently for familiar molecules, i.e . for pyrrole-2-carboxylic acid and formic acid dimers, containing as well the two equivalent O---HO interactions, supported further by RAHB contribution [57, 58]. In these studies the electronic enthalpies (per one O---HO hydrogen bond) are−5.8 kcal mol −1 and−8.5 kcal mol −1 for formic and pyrrole-2-carboxylic dimers, respectively.…”
Section: Resultsmentioning
confidence: 70%
“…Such a reduction is of course accompanied by a concomitant increase in the total number of localised electrons, and becomes a powerful argument against the traditional role assigned to resonance in RAHBs, in agreement with previous experimental and theoretical studies which found no indication of an increased electron delocalisation in these types of H-bonds. [29][30][31][32][33][36][37][38][39][40] Since, as stated above, the interacting quantum atom partition provides a unique combination of electron and energy descriptors, we may now explore the energy features of the formation of the HB associated with the previously discussed changes in R(r) and R 2 (r 1 ,r 2 ). Following the previous line of reasoning, we first examine the energetics of resonance and bond order equalization, which are indicated in terms of the covalent, i.e.…”
Section: Resultsmentioning
confidence: 99%